Produção de concentrado proteico e lactose de soro de leite por processos de separação por membranas - Seguenka, Bruna (2016)
Whey is the liquid generated in the production of cheese. It contains about 50% of the solids present in milk, including 20% of protein, over 99% of the lactose and some of the minerals and water soluble vitamins. It is estimated that the whey generated in 2014 was 6,6 million tons. For each liter of whey approximately 50 g of lactose and 10 g of protein (high nutritional and functional value) are lost. Whey is a by-product of the agroindustrial which has a great potential for further use, since only 50 % of the volume produced is reused. Despite their inclusion in various food products, the liquid whey or in powder form has low commercial value, without aggregation of the same value. The objective was to obtain an integrated process fractioning of whey constituents, for obtaining whey protein concentrate (WPC), concentrated lactose (CL) and minimize water spent in the process. The whey fractionation it occurred by membrane separation processes: WPC production by ultrafiltration from the whey and nanofiltration for the production of CL from the ultrafiltration permeate, employing steps diafiltration (DF) after the concentration of the components, to obtain higher purity. The reduction in consumption water in the process proceeded to realizing the treating the diafiltration permeated by reverse osmosis. The products were characterized by their physicochemical properties. The results demonstrated that the ultrafiltration, followed by diafiltration separates the whey proteins reducing 100 % lactose and 78 % of ash the whey, yielding a WPC with 89.95 % protein, dry basis. The nanofiltration, followed by diafiltration, concentrated the lactose, and reduced 84 % of monovalent ions present in the ultrafiltration permeate, yielding an CL with 95 % of lactose, on dry base. The application of reverse osmosis become liable to reuse the DF permeate and allowed a reduction of 41 % of pure water consumption in the process. The results showed the feasibility of using ultrafiltration and nanofiltration, integrated with steps of diafiltration, to fractionate serum components, adding value to this by-product and recognizing the whey as an important raw material for the milk chain.